World War I and propaganda - Paddock, Troy R. E. (History of warfare, 2014)
World War I and Propaganda offers a new look at a familiar subject. Scholars examine the complex negotiations involved in propaganda within the British Empire, in occupied territories, in neutral nations, and how war should be conducted.